Silencing of PCK1 mitigates the proliferation and migration of vascular smooth muscle cells and vascular intimal hyperplasia by suppressing STAT3/DRP1-mediated mitochondrial fission - Zhang Li; Chen Yingmei; Pan Quanrong; Fang Shizheng; Zhang Zhongjian; Wang Jia; Yang Yongjian; Yang Dachun; Sun Xiongshan (Acta Biochimica et Biophysica Sinica)
The pathological proliferation and migration of vascular smooth muscle cells (VSMCs) are key processes during vascular neointimal hyperplasia (NIH) and restenosis. Phosphoenolpyruvate carboxy kinase 1 (PCK1) is closely related to a variety of malignant proliferative diseases. However, the role of PCK1 in VSMCs has rarely been investigated. This study aims to examine the role of PCK1 in the proliferation and migration of VSMCs and vascular NIH after injury. In vivo, extensive NIH and increased expression of PCK1 within the neointima are observed in injured arteries. Interestingly, the administration of adeno-associated virus-9 (AAV-9) carrying Pck1 short hairpin RNA (shPck1) significantly attenuates NIH and stenosis of the vascular lumen. In vitro, Pck1 small interfering RNA (siPck1)-induced PCK1 silencing inhibits VSMC proliferation and migration. Additionally, silencing of PCK1 leads to reduced expression of dynamin-related protein 1 (DRP1) and attenuated mitochondrial fission. Lentivirus-mediated DRP1 overexpression markedly reverses the inhibitory effects of PCK1 silencing on VSMC proliferation, migration, and mitochondrial fission. Finally, PCK1 inhibition attenuates the phosphorylation of signal transducer and activator of transcription 3 (STAT3). Activation of STAT3 abolishes the suppressive effects of PCK1 silencing on DRP1 expression, mitochondrial fission, proliferation, and migration in VSMCs. In conclusion, PCK1 inhibition attenuates the mitochondrial fission, proliferation, and migration of VSMCs by inhibiting the STAT3/DRP1 axis, thereby suppressing vascular NIH and restenosis.